ʈiič-mɑɫ-ɴi : sharing drowning prevention with Nuu-chah-nulth First Nations - Carswell, Emily Dawn (2018)
The Nuu-chah-nulth First Nations traditional territory borders the west coast of Vancouver Island in British Columbia, Canada. This case study describes how the knowledge, traditional practices, and cultural wisdom of Nuu-chah-nulth First Nations community members regarding water safety and canoeing safety informed two offerings of the Swim to Survive program for the children of Hesquiaht, and Tla-o-qui-aht First Nations. Swim to Survive is a drowning prevention program offered by the Lifesaving Society of Canada. These iterations were designed in collaboration with community input by cultural teachers who shared their ancestral teachings and equipment, and with the support of local Nuu-chah-nulth leaders in education, recreation, and health care. The community members were taught by certified lifeguards, and swimming instructors qualified by The Lifesaving Society. Through this exploration, a more culturally sensitive program began to take shape that was appropriate to these communities with the understanding that what was relevant to one nation may not be culturally relevant to another and that each nation has unique practices and needs.